Power quality improvement in grid connected hybrid renewable energy system using UPQC - Singh, Manpreet; Singh, Lakhwinder (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The detection and mitigation of power quality issues have become essential due to the increased interest in integrating renewable energy sources to the power system. There are various methods to mitigate the power quality issues that arise due to the integration of composite renewable sources into the current power system. Distribution flexible alternating current transmission system (D-FACTS) devices are widely used for this purpose. Unified power quality conditioner (UPQC), due to its superior performance over other conditioners, has been used in the proposed system. The primary objective of this paper is to implement the UPQC to enhance power quality in grid-integrated photovoltaic-wind system by reducing total harmonic distortion (THD). MATLAB Simulink is utilized to verify the results of the proposed system. Total harmonic distortion analysis for a grid-connected photovoltaic-wind system without and with UPQC is compared. The efficacy of UPQC in reducing THD in a grid-integrated photovoltaic-wind system is presented. THD decreases from 24.06% to 11.19% when UPQC is linked to the proposed system. To validate the implementation of the proposed system, the results are compared with already published work.